ENVIRONMENTAL SCIENCE AND SUSTAINABLE DEVELOPMENT: BEHAVIORAL TRANSFORMATION TO KNOWLEDGE SYSTEM INTEGRATION FOR SUSTAINABILITY ACTION - Sodri, Ahyahudin; Herdiansyah, Herdis (Journal of Environmental Science and Sustainable Development, 2025)
Sustainability issues are now a global concern. However, knowing the root causes of problems and the target is not the only factor that constantly motivates change for the better (Wamsle & Osberg, 2022) as such change also requires encouragement from actors, including individuals, organizations, and communities. Therefore, the human aspect is crucial for the successful achievement of sustainability (Hariram et al., 2023). In other words, questions on sustainability are not just about "what should be done?" and also on “how to get people to do it?” and “why are currently available interventions not yet fully utilized?” Such is required reflecting the findings of a body of previous research which accentuates that our main struggle in the global era we already in, is the discrepancy between awareness and action, between policy and practice, between scientific knowledge and behavior (Hariram et al., 2023; Kirchner-Krath et al., 2024). Global sustainability efforts often promoted into green technologies and environmental policies. It has shown that even well-designed interventions, the result not always in meaningful change. In several countries, some initiatives have fallen short because they overlook the psychological and socio-cultural factors that shape individual behavior and collective decision-making (de Costa et al., 2025). It also requires a deep understanding of community perspectives as expressed through local social norms and everyday practices. As a result, the presence of infrastructure or the financial support mechanism alone is not enough to drive meaningful change (Kinzig et al., 2013). Local context is another critical factor that shape adoption behavior and the extent to which proposed solutions are accepted and supported (Carmen et al., 2024; Syamsiyah et al., 2025). In this context, a more comprehensive understanding of environmental science is required. With the philosophy of environmental science, humans constitute is one of the three core dimensions, together with environmental and economic factors, and any effective approach that must balance to these elements. However, when modern environmental science, characterized by data analyses and methodologies is applied in practice, it often meets tensions with deeply rooted local and traditional knowledge systems that have shaped people’s perceptions and behaviors for generations (Ijatuyi et al., 2025). A clear example can be found in Bali, where the Subak irrigation system and the Danu Kerthi philosophy have guided water management for centuries. These practices represent living environmental systems rather than merely cultural heritage to be preserved. When traditional approaches are used into environmental science, conservation efforts are often more effective, as they are grounded in community acceptance and sustained through active local participation (Morse, 2025). This integration can serve as a recognition that centuries-old knowledge systems have legitimacy and effectiveness that must be combined with scientific monitoring and formal governance to achieve optimal conservation outcomes. Beyond the local context, the organizational context, both in the public and private sectors, can also act as a transformative agent in driving individual practices (Borrás et al., 2024; Keil et al., 2025). Green human resource management (GHRM) integrates environmental and individual lifecycle goals within an organization. This approach demonstrates how integrating understandings of desires can influence individual behaviour and drive organizational innovation that contributes to sustainability (Ahmad et al., 2025; Borrás et al., 2024; Keil et al., 2025; Shoaib et al., 2025). This 15th issue of the Journal of Environmental Science and Sustainable Development focuses on an often overlooked yet fundamental dimension of sustainability: the ways in which human behavior, cultural and spiritual value systems, local institutional contexts, and the integration of traditional knowledge with modern science collectively shape sustainable landscapes. Unlike previous editions that highlight biophysical and techno-ecological aspects, this issue shifts attention into questions of agency, motivation, beliefs, norms, and meaningful systems that highlight environmental decisions and actions. This perspective shows the critical need for interdisciplinary approaches to explaining contemporary sustainability challenges. Environmental issues today extend beyond ecological degradation to include human behavior and the capacity of diverse knowledge systems, scientific, local, and policy-based, to interact and function cohesively. Consequently, behavioral transformation supported by the integration of multiple knowledge systems represents a fundamental pathway toward effective, adaptive, and long-term sustainability action. The articles in this issue explore diverse geographic and sectoral contexts, ranging from the application of green transportation technologies, air management in urban-industrial versus traditional-tourism contexts, climate adaptation in agricultural communities, global natural resource management (GHRM) practices in the tourism sector, to indigenous wisdom-based lake conservation and sustainable food systems.